Circular intermediate-mediated horizontal transfer of the chromosome-encoded cfr(C) gene in multi-drug resistant Campylobacter coli from swine sources - An, Jae-Uk; Lee, Soomin; Guk, Jae-Ho; Woo, Jungha; Song, Hyokeun; Cho, Seongbeom (Frontiers in Microbiology, 2023)
Campylobacter is a major zoonotic pathogen that causes gastrointestinal and, rarely, immune diseases in humans. The antimicrobial-resistance gene cfr(C) carried by Campylobacter and is a cfr-like gene that targets bacterial 23S rRNA through A2503 methylation. cfr(C) confers cross-resistance to five antimicrobial classes (PhLOPSA), including lincosamide, streptogramin A, and pleuromutilin, which are classified as critically important antimicrobials to human by the World Health Organization. To elucidate the genetic variation and horizontal transfer mechanism of cfr(C), we analyzed the genetic background and horizontal transfer unit of Campylobacter-derived cfr(C) through comparative genomic analysis. We identified nine cfr(C)-positive C. coli strains of 157 strains isolated from swine sources. Three novel cfr(C) gene single nucleotide polymorphism (SNP) sites (19delA, 674C > A, and 890 T > C) were identified from nine cfr(C)-positive strains. Among six identified cfr(C) SNP variant types (SNP-I to -VI), five types of randomly inserted cfr(C)-cassettes on chromosome and one type of plasmid-like element were identified, their gene cassette composition differing depending on the cfr(C) variants. Three of six cfr(C) cassette types contained aminoglycoside-streptothricin resistance cluster “aphA3-sat4-aadE.” The cfr(C) gene cassette with pcp gene (GC-1, GC-4, and GC-5) formed a pcp-mediated circular intermediate “pcp-hp-cfr(C)-aphA3,” which has not been previously reported. Other two cfr(C) cassette-types with ISChh1 formed circular intermediate “ISChh1-aphA3-cfr(C)-lnu (G)-pnp-ant1-hp-ATPase” and “ISChh1-aphA3-cfr(C)-hp.” In conjugation assay, the pcp-mediated circular intermediate was naturally transferred to the plasmid of recipient C. coli wild-type strain from swine source, and comparative genomic analysis revealed that cfr(C) encoded in pcp-mediated circular intermediate was inserted into the plasmid of recipient by homologous recombination with pcp and aphA3. This study revealed that novel multidrug resistance gene cfr(C) carried by C. coli from swine sources can be highly genetically diverse and transferable. Moreover, we suggest that the transferability of chromosomal cfr(C) may contribute to the global spread of multidrug resistance against clinically important antimicrobials.